A novel strategy to improve the compressive characteristic and flexural stiffness of the metallic lattices by introducing the CFRP composite surfaces. (March 2023) - Wang, Zhuangzhuang; Cao, Xiaofei; Zheng, Qiuyao; Ma, Binlin; Ren, Xianben; Huang, Zhixin; Li, Ying
Abstract: Design of high-strength lightweight structure was an urgent demand in today's engineering applications. In order to meet the lightweight design requirements of the structure, the pipe wall of the tubular structure was designed as body-centred cubic (BCC) shape. By carrying out axial compression and three-point bending tests, the strength value, total energy absorption and specific energy absorption of BCC tube under different directions of loading were analyzed. However, it was concluded that the mechanical properties of BCC tube under two loading conditions were poor. Next, in order to improve the mechanical properties of BCC pipes, we add Carbon Fiber Reinforced Plastic (CFRP) pipes outside BCC pipes to form body centered BCC/CFRP reinforced plastic pipes. Through the same test method, the strength value, total energy absorption ( EA ) and specific energy absorption ( SEA ) of the mixed pipe under different directions of loading were analyzed. Through comparative analysis, it can be seen that adding CFRP pipe can greatly improve the mechanical properties of BCC pipe with small mass change. By comparing the deformation modes of the two pipes, it can be seen that the interaction of the two pipes can greatly improve the deformation of BCC pipes, and then improve the mechanical properties of BCC pipes. Graphical Abstract: ga1 Highlights: Static axial crushing and three-point bending of BCC and BCC/CFRP hybrid square tubes were investigated. Adding CFRP pipe can greatly improve the mechanical properties of BCC pipe.